2007
DOI: 10.1002/jor.20456
|View full text |Cite
|
Sign up to set email alerts
|

Functional tissue engineering for tendon repair: A multidisciplinary strategy using mesenchymal stem cells, bioscaffolds, and mechanical stimulation

Abstract: Over the past 8 years, our group has been continuously improving tendon repair using a functional tissue engineering (FTE) paradigm. This paradigm was motivated by inconsistent clinical results after tendon repair and reconstruction, and the modest biomechanical improvements we observed after repair of rabbit central patellar tendon defects using mesenchymal stem cell-gelsuture constructs. Although possessing a significantly higher stiffness and failure force than for natural healing, these first generation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
273
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(285 citation statements)
references
References 24 publications
4
273
0
8
Order By: Relevance
“…Tissue engineers are incorporating mechanical stimulation to enhance tendon tissue augmentations and replacements [134][135][136][137][138][139][140][141][142][143][144][145][146] . By mechanically preconditioning the tissue-engineered construct cell population prior to in vivo implantation, the cells may be better equipped to enhance the repair since they have been exposed to the appropriate mechanical environment 134,135 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineers are incorporating mechanical stimulation to enhance tendon tissue augmentations and replacements [134][135][136][137][138][139][140][141][142][143][144][145][146] . By mechanically preconditioning the tissue-engineered construct cell population prior to in vivo implantation, the cells may be better equipped to enhance the repair since they have been exposed to the appropriate mechanical environment 134,135 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
“…Given the importance of physiological loading to maintain tendon homeostasis, investigators have shown that applying load promotes a tendon-like phenotype in both two and threedimensional culture conditions [139][140][141][142][143][144][145][146] . Ralphs et al showed that when tendon cells are cultured on a two-dimensional substrate and subjected to biaxial strain at 1 Hz for eight hours per day for a total of ninety-six hours, cells link together using actin adherens junctions along the principal line of strain to monitor tensile load 142 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
“…Given that tissue graft based therapies have failed to restore native tendon function, it is anticipated that the tissue-engineering arpeggio (scaffolds, cells, biologics alone or in combination) would provide a functional therapy in the years to come [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Such combined tissue-engineered therapies also have significant potential in the bioengineering of tendon. 29 Preliminary data from our group have been promising, showing that GDF-5 treatment leads to increases of overall proliferation, total DNA, hydroxyproline (OHP), and glycosaminoglycan (GAG) expression of rat ADMSCs. 30,31 However, the effect of GDF-5 on the tendonogenic differentiation of ADMSCs has not yet been fully investigated.…”
mentioning
confidence: 99%